The Genetic Links to Anxiety and Depression (GLAD) Study: Online recruitment into the largest recontactable study of depression and anxiety - Davies, Molly R.; Kalsi, Gursharan; Armour, Chérie; Jones, Ian R.; McIntosh, Andrew M.; Smith, Daniel J.; Walters, James T.R.; Bradley, John R.; Kingston, Nathalie; Ashford, Sofie; Beange, Ioana; Brailean, Anamaria; et al. (Behaviour research and therapy, 2019)
Anxiety and depression are common, debilitating and costly. These disorders are influenced by multiple risk factors, from genes to psychological vulnerabilities and environmental stressors, but research is hampered by a lack of sufficiently large comprehensive studies. We are recruiting 40,000 individuals with lifetime depression or anxiety and broad assessment of risks to facilitate future research. The Genetic Links to Anxiety and Depression (GLAD) Study (www.gladstudy.org.uk) recruits individuals with depression or anxiety into the NIHR Mental Health BioResource. Participants invited to join the study (via media campaigns) provide demographic, environmental and genetic data, and consent for medical record linkage and recontact. Online recruitment was effective; 42,531 participants consented and 27,776 completed the questionnaire by end of July 2019. Participants’ questionnaire data identified very high rates of recurrent depression, severe anxiety, and comorbidity. Participants reported high rates of treatment receipt. The age profile of the sample is biased toward young adults, with higher recruitment of females and the more educated, especially at younger ages. This paper describes the study methodology and descriptive data for GLAD, which represents a large, recontactable resource that will enable future research into risks, outcomes, and treatment for anxiety and depression. •Online recruitment of 40,000 individuals with lifetime depression or anxiety.•Detailed online phenotyping combined with genetic and clinical data.•The study sample is severe, highly comorbid, with chronic psychopathology.•The study protocol enables recall of participants for future research and trials.